Multiphysics simulations: Challenges and opportunities. (February 2013) - Keyes, David E; McInnes, Lois C; Woodward, Carol; Gropp, William; Myra, Eric; Pernice, Michael; Bell, John; Brown, Jed; Clo, Alain; Connors, Jeffrey; Constantinescu, Emil; Estep, Don; et al.
We consider multiphysics applications from algorithmic and architectural perspectives, where "algorithmic" includes both mathematical analysis and computational complexity, and "architectural" includes both software and hardware environments. Many diverse multiphysics applications can be reduced, en route to their computational simulation, to a common algebraic coupling paradigm. Mathematical analysis of multiphysics coupling in this form is not always practical for realistic applications, but model problems representative of applications discussed herein can provide insight. A variety of software frameworks for multiphysics applications have been constructed and refined within disciplinary communities and executed on leading-edge computer systems. We examine several of these, expose some commonalities among them, and attempt to extrapolate best practices to future systems. From our study, we summarize challenges and forecast opportunities.